OUTH WINDS OVER THE CANTABRIAN-WESTERN PYRENEAN REGION (CWP): FREQUENCY AND CLIMATE INFLUENCE. - San Martin Orbe, Kepa (Geographicalia, 2021)
The South Wind flows, especially during the autumn-winter period, generate a great thermo-hygrometric influence (tempering and reducing relative humidity) on the climatic conditions of the geographical region formed around the central axis of the Bay of Biscay, that extends from its peninsular slope (eastern Cantabrian strip) towards the continental zone (New Aquitaine) and located to the lee of the orographic complex that structures the Eastern Cantabrian Mountains, the Basque Mountains and the Western or Atlantic Pyrenees. The statistical analysis of the daily records of South Wind and the correspondence of these with the respective data for other climatic variables, specifically for the decade of 1961-1971 in which a high count of negative annual values ​​of the index of the North Atlantic Oscillation (NAO) is observed and provides very significant conclusions regarding the climatic effect on the study region that we have called Cantabrian-Western Pyrenees. The teleconnection processes between the ocean-atmospheric weather patterns that determine the different types of atmospheric circulation in the entire North Atlantic region, constitute an equally determining factor (together with other agents such as solar radiation, orographic structure, etc.) of the climatic variability characteristic of the North Atlantic-Europe region (ANE). Therefore, the multiple investigations on teleconnection and correlation processes between these climatic patterns progressively provide more precise mechanisms to explain and predict circulatory and climatic variability over the region. In our analysis of the correlation and association between only two of the ocean-atmospheric phenomena with the highest climatic incidence in the region, the El Niño-Southern Oscillation (NOI) phenomenon and the oceanic pressure pattern known as the North Atlantic Oscillation (NAO ) we provide a simple, but significant, sample of what these teleconnection processes suppose when analysing, reconstructing and predicting the atmospheric circulation conditions that configure and characterize the climatic variability of the southwestern European façade and therefore of the region study. Keywords: South Wind, Cantabrian-Western Pyrenean region, weather patterns and teleconnection, statistical correlation of NOI-NAO indices.